lncRNA HOTTIP Recruits EZH2 to Inhibit PTEN Expression and Participates in IM Resistance in Chronic Myeloid Leukemia - Jing Liu; Lin Yang; Xiaojun Liu; Lu Liu; Menghan Liu; Xuefeng Feng; Jianmin Luo (Stem Cells International)
Objective. To investigate that HOTTIP suppressed PTEN gene expression and was involved in IM resistance in chronic myeloid leukemia through recruitment of EZH2 protein. Methods. Seventy-one cases of bone marrow monocytes diagnosed with CML in the Second Hospital of Hebei Medical University from 2018 to 2021 were selected. These patients were diagnosed with CML by bone marrow morphology, immunology, molecular biology, and cytogenetics, of which 36 were sensitive to IM and 35 were resistant to IM. We selected K562 and IR-K562 cells preserved in the laboratory as our subjects to study the expression levels of HOTTIP in the bone marrow cells of IM CML-resistant patients and IM-resistant cells. Results. In this study, we found that HOTTIP was highly expressed in the bone marrow and cell lines of CML patients resistant to Imatinib mesylate (IM). In in vitro experiments, lentiviral knockdown of HOTTIP inhibited CML cell proliferation and promoted apoptosis, and knockdown of HOTTIP also increased sensitivity to IM. Mechanistically, highly expressed HOTTIP is involved in the biological process of IM resistance by recruiting Zeste homologous protein 2 enhancer (EZH2) to inhibit the expression of phosphatase and Tensin homologous protein (PTEN) genes. Conclusions. We confirmed that HOTTIP and EZH2 are highly expressed in IM-resistant patients and IM-resistant CML cell lines. In CML cell lines, HOTTIP is involved in regulating the proliferation and apoptosis of CML cells and resistance to IM.